Personalized Risk–Benefit Ratio Adaptation of Breast Cancer Care at the Epicenter of COVID‐19 Outbreak. (26th May 2020) - Viale, Giulia; Licata, Luca; Sica, Lorenzo; Zambelli, Stefania; Zucchinelli, Patrizia; Rognone, Alessia; Aldrighetti, Daniela; Di Micco, Rosa; Zuber, Veronica; Pasetti, Marcella; Di Muzio, Nadia; Rodighiero, Mariagrazia; et al.
Abstract: : Northern Italy has been one of the European regions reporting the highest number of COVID‐19 cases and deaths. The pandemic spread has challenged the National Health System, requiring reallocation of most of the available health care resources to treat COVID‐19‐positive patients, generating a competition with other health care needs, including cancer. Patients with cancer are at higher risk of developing critical illness after COVID‐19 infection. Thus, mitigation strategies should be adopted to reduce the likelihood of infection in all patients with cancer. At the same time, suboptimal care and treatments may result in worse cancer‐related outcome. In this article, we attempt to estimate the individual risk–benefit balance to define personalized strategies for optimal breast cancer management, avoiding as much as possible a general untailored approach. We discuss and report the strategies our Breast Unit adopted from the beginning of the COVID‐19 outbreak to ensure the continuum of the best possible cancer care for our patients while mitigating the risk of infection, despite limited health care resources. Implications for Practice: Managing patients with breast cancer during the COVID‐19 outbreak is challenging. The present work highlights the need to estimate the individual patient risk of infection, which depends on both epidemiological considerations and individual clinical characteristics. The management of patients with breast cancer should be adapted and personalized according to the balance between COVID‐19‐related risk and the expected benefit of treatments. This work also provides useful suggestions on the modality of patient triage, the conduct of clinical trials, the management of an oncologic team, and the approach to patients' and health workers' psychological distress. Abstract : This article discusses strategies employed by an institution in Northern Italy to ensure the continuum of the best possible cancer care during the COVID‐19 pandemic for breast cancer patients while mitigating the risk of infection, despite limited healthcare resources.